EVALUASI PROGRAM KELURAHAN TANGGUH BENCANA DI KOTA PADANG - rimala salwa; Zikri Alhadi (Laboratorium Jurusan Ilmu Administrasi Negara Fakultas Ilmu Sosial Universitas Negeri Padang, 2019)
The purpose of this study was to evaluate or assess whether the program of disaster resistance subdistrict has run optimally and whether the program was feasible to continue. This research was a qualitative research with descriptive method. The selection of informants was done through purposive sampling. Data were collected through interviews and documentation studies; then the data were analysied through presenting data, data reduction, and verification of data. The instruments used in this study were the researchers themselves, interview guides in the form of granules of questions that had been prepared, while to support documentation related to research eating data collection tools that I use are cameras, mobile phones, and recording devices that are useful for recording interviews with informants so that it can facilitate the compilation of data and the validity tested of this data used source triangulation technique, and than the data were analyzed with qualitative data technique. So that the results of this study can be concluded that the program that had been did in Lolong Belanti Village of Padang City had not optimally and the objectives of the program had not been achieved as a whole.